Afinidades y tensiones entre religión y política en las trayectorias de los militantes de la juventud obrera católica en bahía blanca (1968-1975) = Affinities and tensions between religion and politics in the trajectories of the militants of the Catholic worker youth in Bahia Blanca (1968-1975) - Dominella, Virginia Lorena (Ciencias sociales y religión, 2014)
This article aims to reconstruct and analyzethe relationship between religion and politics in the experience of the members of the Juventud Obrera Católica in Bahía Blanca(Argentina) among 1968 and 1975. In this sense, it tries to reflect upon the following questions: How do they experiencetheir approach to social action, as well as political militancy? To what extent this process was motivated by their faith? In what way their participation in the catholic groups had influence in their militant itineraries? What kind of tensions emerged from the religious and political options?